2018
DOI: 10.1002/jcla.22692
|View full text |Cite
|
Sign up to set email alerts
|

Global expression profiling of metabolic pathway‐related lncRNAs in human gastric cancer and the identification of RP11‐555H23.1 as a new diagnostic biomarker

Abstract: Background: Long noncoding RNAs (lncRNAs) have roles in regulating metabolism; however, the global expression profile of metabolic pathway-associated lncRNAs in gastric cancer is unknown. The purpose of our study was to examine metabolic pathway-related lncRNAs in gastric cancer and their possible diagnostic values. Methods: Differential expression patterns of metabolic pathway-related lncRNAsbetween gastric cancer and paired nontumor tissues were detected using metabolic pathway-associated lncRNA microarrays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
1
28
1
Order By: Relevance
“… Some of lncRNAs were even indeed considered as biomarkers for diagnosis or prognosis of GC . For instance, a metabolism‐related lncRNA, RP11‐555H23.1 , was found to be a potential diagnostic biomarker in GC . Also, the expression level of H19 in plasma could be served as a biomarker for patients with GC .…”
Section: Discussionmentioning
confidence: 99%
“… Some of lncRNAs were even indeed considered as biomarkers for diagnosis or prognosis of GC . For instance, a metabolism‐related lncRNA, RP11‐555H23.1 , was found to be a potential diagnostic biomarker in GC . Also, the expression level of H19 in plasma could be served as a biomarker for patients with GC .…”
Section: Discussionmentioning
confidence: 99%
“…The detection of piRNA-1245 in GJ could be a new avenue for differentiating GC from healthy people. [24][25][26][27][28][29] Some altered ncRNAs played a crucial role in the regulation of malignant phenotypes of tumor. 24 Mo et al elucidated that lncRNA RP11-555H23.1 showed an important role in the occurrence of GC, and used as a new marker of GC.…”
Section: Accumulating Literatures Showed That Alternation Of Non-codingmentioning
confidence: 99%
“…24 Mo et al elucidated that lncRNA RP11-555H23.1 showed an important role in the occurrence of GC, and used as a new marker of GC. 26 Zhu et al 29 identified that tiRNA-5034-GluTTC-2 might be responsible for a marker for GC diagnosis. Tan et al established that detection of miR-145 and miR-185 might be helpful for predicting adverse reactions and effectiveness of SOX regimen against GC.…”
Section: Accumulating Literatures Showed That Alternation Of Non-codingmentioning
confidence: 99%
“…Gastric cancer (GC) is the fourth global malignant tumors and the fourth leading cause of cancer‐related death worldwide, especially in Eastern Asian countries . Though the overall survival of GC patients to some extent has improved due to the application of early detection technology and radical surgery, most early‐stage gastric cancer (EGC) patients have no characteristic manifestations, and many patients are still diagnosed at the advanced stages and miss the best chance to therapy . Nowadays, upper gastrointestinal (GI) endoscopy followed by pathologic examination remains the golden standard for the diagnosis of GC .…”
Section: Introductionmentioning
confidence: 99%
“…1 Though the overall survival of GC patients to some extent has improved due to the application of early detection technology and radical surgery, most early-stage gastric cancer (EGC) patients have no characteristic manifestations, and many patients are still diagnosed at the advanced stages and miss the best chance to therapy. 2 Nowadays, upper gastrointestinal (GI) endoscopy followed by pathologic examination remains the golden standard for the diagnosis of GC. 3 However, upper GI endoscopy is not a routine medical examination in most countries, and making a gastroscopy inspection is an invasive technique that will sometimes make patients uncomfortable.…”
Section: Introductionmentioning
confidence: 99%